2021
DOI: 10.1038/s41598-021-87129-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling biomass allocation strategy of young planted Zelkova serrata trees in Taiwan with component ratio method and seemingly unrelated regressions

Abstract: Trees accumulate biomass by sequestrating atmospheric carbon and allocate it to different tree components. A biomass component ratio is the ratio of biomass in a tree component to total tree biomass. Modeling the ratios for Zelkova serrata, an important native reforestation tree species in Taiwan, helps in understanding its biomass allocation strategy to design effective silvicultural treatments. In this study, we applied Component Ratio Method (CRM) to relate biomass component ratios of main stem, large branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This may be due to different growth strategies between the two species. Chen et al (2021) showed that a nine-year old single species Z. serrata plantation displayed significant stratification in stand structures due to strong inter-tree competition. In early stand development, dominant Z. serrata trees quickly reach upper strata by investing greater energy in crown development (Chen et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be due to different growth strategies between the two species. Chen et al (2021) showed that a nine-year old single species Z. serrata plantation displayed significant stratification in stand structures due to strong inter-tree competition. In early stand development, dominant Z. serrata trees quickly reach upper strata by investing greater energy in crown development (Chen et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2021) showed that a nine-year old single species Z. serrata plantation displayed significant stratification in stand structures due to strong inter-tree competition. In early stand development, dominant Z. serrata trees quickly reach upper strata by investing greater energy in crown development (Chen et al 2021). As a result, dominant Z. serrata trees develop large crowns, which in turn leads to rapid diameter and height growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particular attention was taken to avoid a dense plantation scheme [48]. The prescribed number of living plants per m 2 must be clearly indicated as well as their typology [59]. Specific climatic and soil conditions should be also taken into account, as the reforestation model must consider the different regions where it is applied and carefully select the autochthonous vegetation [60].…”
Section: Estimate Of the Carbon Sink Through Reforestationmentioning
confidence: 99%